2009
DOI: 10.1103/physrevb.80.155445
|View full text |Cite|
|
Sign up to set email alerts
|

Wrinkling of monolayer graphene: A study by molecular dynamics and continuum plate theory

Abstract: Wrinkling was observed for a circular monolayer graphene sheet in nanoindentation based on moleculardynamics simulations. The mechanics fundamentals of this phenomenon were then explored using a twodimensional plate model. It was found that the graphene wrinkles when the indentation depth reaches a critical value, the wrinkling is induced by the circumferential compression in the graphene, and the bending stiffness of the graphene sheet plays an essential role in stabilizing its one-atom layer nanostructures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 48 publications
0
42
1
Order By: Relevance
“…Those wrinkles can be obtained by various external loads. Wang [26] utilized an indenter trip tip of diameter 0.535nm…”
Section: Introductionmentioning
confidence: 99%
“…Those wrinkles can be obtained by various external loads. Wang [26] utilized an indenter trip tip of diameter 0.535nm…”
Section: Introductionmentioning
confidence: 99%
“…9 Numerical simulations have been done to understand the formation of wrinkles and their impact on graphene. [10][11][12][13] Wrinkles are commonly found in chemical-vapor-deposition (CVD) grown graphene that is transferred to other substrates. [14][15][16][17] In CVD, graphene wrinkles are formed at metal step edges due to thermal stress.…”
mentioning
confidence: 99%
“…On the other hand, molecular dynamics (MD) simulations have often been employed for scales of length much smaller than micrometers, due to the intractable computational expense that would be incurred for a direct experimental comparison. There have been numerous examples of MD simulations of nanoindentation of a variety of nanometer materials [4][5][6]. However, to the authors' knowledge, no atomistic simulation of the pressure bulge test has been reported for the analysis of the nonlinear elastic properties of atomic layers, in particular nanometer-sized graphene monolayers, which motivates the current study.…”
Section: Introductionmentioning
confidence: 96%